(3GdeYeQjfs - (3jMji Hf YHO GdhgGH Hf eMeO ESMGb eMeO Hf jMji Hf efOg GdCUHgGfj GdYHOj,J (B511 (3g` s
(3ChdgG (B:s
(3SCdJ QMefG Gddg hEjGc Cf CLeY dc ef HdZJ eOg YeQg eGFI hYTQjf SfI ef CUMGH QShd Gddg Udi Gddg Ydjg hSde, aCLHJc Edi Pdc s
(3Vef eLehY , JQJjHgG (B: (3ef U (B18 (3C (B- (3U(B21 (3Cs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B156 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B210s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B151 s
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(624(3)) s
Keywords: (3GdJGQjNs